Exploring Factors Enhancing English Speaking Proficiency - Laksmi Gasani; Muhammad Anjar Nugraha; Dody Wahyudi Purnama (Universitas Subang, 2025)
Despite increased exposure to English in Indonesia’s digital era, speaking proficiency remains very limited among students. The 2024 EF English Proficiency Index highlights Indonesia’s relatively low ranking compared to other Asian countries like the Philippines and Malaysia. Since English-speaking proficiency is essential for global communication, personal growth, careers, and educational opportunities, understanding the factors that enhance it is crucial. This qualitative study explores factors enhancing English-speaking proficiency and identifies the most influential ones that help students become more proficient. Participants included three college students who consistently achieved high scores in their English-speaking class and their lecturer at Subang University. Data were collected through semi-structured interviews and classroom observations. The findings reveal that age, positive attitudes, family support, personality, language exposure, teachers, and regular practice contribute to proficiency, with language exposure, personality, teachers, and regular practice being the most influential. This study provides insights to help students develop self-confidence, take risks, practice consistently, and openness to diverse language exposure, ultimately improving their English-speaking proficiency.